Isu Etika dan Privasi dalam Penggunaan Chatbot Berbasis Kecerdasan Buatan - Sherly Dea Aulia; Adelia Noviyanti; Rahcesa Sabell Gusti (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2025)
This study examines ethical and privacy issues in the use of AI-based chatbots by employing the Grounded Theory Literature Review (GTLR) method. Using systematic analysis of conference papers published between 2015–2025, the study identifies core themes related to data protection, user consent, transparency, and security risks in conversational AI. Literature reviewed highlights recurring concerns including data leakage, misuse of personal information, algorithmic bias, and lack of regulatory clarity. The findings show that ethical considerations extend beyond technical safeguards, demanding responsible system design and user awareness. Privacy issues emerge from users’ limited understanding of how their data is collected and utilized, while security threats involve adversarial attacks and extraction risks in large language models. The study concludes that integrating ethical principles with robust security mechanisms is essential to ensure safe and trustworthy chatbot deployment.